1996
DOI: 10.1074/jbc.271.9.4937
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, Biochemical, and Electrophysiological Characterization of Drosophila norpA Mutants

Abstract: Inositol phosphate signaling has been implicated in a wide variety of eukaryotic cellular processes. In Drosophila, the phototransduction cascade is mediated by a phosphoinositide-specific phospholipase C (PLC) encoded by the norpA gene. We have characterized eight norpA mutants by electroretinogram (ERG), Western, molecular, and in vitro PLC activity analyses. ERG responses of the mutants show allele-dependent reductions in amplitudes and retardation in kinetics. The mutants also exhibit allele-dependent redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(46 citation statements)
references
References 50 publications
3
43
0
Order By: Relevance
“…In contrast, the optic lobes are widely labelled but a role for visual information in the female in this behavioural context has not been reported. To investigate whether the inability to process visual stimuli could explain the reduced mating, we tested the no receptor potential A (norpA ) mutant flies, that have no phototransduction43. We observed that the mating of these flies is not changed (Figure S1c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the optic lobes are widely labelled but a role for visual information in the female in this behavioural context has not been reported. To investigate whether the inability to process visual stimuli could explain the reduced mating, we tested the no receptor potential A (norpA ) mutant flies, that have no phototransduction43. We observed that the mating of these flies is not changed (Figure S1c).…”
Section: Resultsmentioning
confidence: 99%
“…Fly strains and sources are as follows: ap md544  60; UAS - Kir2 .140; tub-GAL80 TS  41; UAS-CD8-GFP 61; 20xUAS-CD8-GFP 62; UAS-AUG-DsRed (Kasuya & Iverson, Flybase); Otd-nls:FLPo 44, provided by D. Anderson ; UAS  >  stop  >  CD8-GFP 63 ; UAS  >  stop  >  Kir2 20, provided by Y.N. Jan ; fru LexA  52, provided by D. Mellert ; LexAop-CD2-GFP 64; 8xLexAop2-FLP L 65; UAS-dcr-2 66; UAS-tra-2 IR  66; elav-GAL80 20; repo-GAL80 67, provided by T. Lee ; OK107-GAL4 68; norpA 3643; tub  >  stop  >  GAL80 45; actin5C-GAL4 69; VGlut MI04979 -LexA:QFAD, GAD1 MI09277 -LexA:QFAD, Cha MI04508 -LexA:QFAD 70. Wild-type: Canton-S (CS) and Dickinson Lab (DL).…”
Section: Methodsmentioning
confidence: 99%
“…The predicted mutant protein therefore interrupts the catalytic domain (α/β-barrel, extending from residue 318–682) and lacks the C-terminal tail required for Gq protein interaction and localization of PLC-β to the Rhabdomere (Katan, 1998). In contrast, the other frequently used null allele norpA P24 (or norpA 36 ) carries a 28-bp deletion within exon 10, which results in the absence of the same C-terminal domains, except for retaining the complete catalytic domain (Pearn et al, 1996) (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…Loss of external eyes and ocelli or eliminating opsin-based photoreception via vitamin A depletion or phototransduction mutants reduces light sensitivity of the clock but doesn’t abolish entrainment of locomotor activity rhythms by light (Blaschke et al, 1996; Hu et al, 1978; Ohata et al, 1998; Pearn et al, 1996), which suggests that other photoreceptors function to entrain circadian oscillators in brain pacemaker cells. A screen for mutants that disrupted rhythms in bioluminescence produced by per -luc identified CRYPTOCHROME (CRY) (Emery et al, 1998; Stanewsky et al, 1998), which is an ortholog of blue light photoreceptor cryptochromes in plants (Ahmad and Cashmore, 1993; Lin et al, 1998).…”
Section: Light Entrainment Of the Drosophila Circadian Feedback Lmentioning
confidence: 99%